Effectiveness of behaviour change techniques used in hand hygiene interventions targeting older children – A systematic review. (July 2021) - Watson, Julie; Cumming, Oliver; MacDougall, Amy; Czerniewska, Alexandra; Dreibelbis, Robert
Abstract: Background: Promoting good hand hygiene in older children is an important measure to reduce the burden of common diseases such as diarrhoea and acute respiratory infections. The evidence around what works to change this behaviour, however, is unclear. Objectives: To aid future intervention design and effective use of resources, this review aims to identify the individual components used in hand hygiene interventions and assesses their contribution to intended behavioural change. Methods: We systematically searched seven databases for experimental studies evaluating hand hygiene interventions targeting children (age 5–12) and quantitively reporting hand hygiene behaviour. Interventions in each study were categorised as 'promising', or 'non-promising' according to whether they led to a positive change in the targeted behaviour. Behaviour change techniques (BCTs) were identified across interventions using a standard taxonomy and a novel promise ratio calculated for each (the ratio of promising to non-promising interventions featuring the BCT). 'Promising' BCTs were those with a promise ratio of ≥2. BCTs were ranked from most to least promising. Results: Our final analysis included 19 studies reporting 22 interventions across which 32 unique BCTs were identified. The most frequently used were 'demonstration of the behaviour', 'instruction on how to perform the behaviour' and 'adding objects to the environment'. Eight BCTs had a promise ratio of ≥2 and the five most promising were 'demonstration of the behaviour', 'information about social and environmental consequences', 'salience of consequences', 'adding objects to the environment', and 'instruction on how to perform the behaviour'. Conclusions: Our findings suggest that hand hygiene interventions targeting older children should employ a combination of promising BCTs that ensure children understand the behaviour and the consequences of their hand hygiene habits, appropriate hardware is available, and social support is provided. Researchers are encouraged to consistently and transparently describe evaluated interventions to allow promising components to be identified and replicated. Highlights: Effective and replicable hand hygiene interventions for older children are needed. Interventions should ensure children understand how to perform the behaviour. Information on the social and environmental consequences should be shared. Good hand hygiene should be enabled by the physical and social environment. Future interventions should focus on combining these promising techniques.